The Role of Customer Perceived Value as a Mediator Between Price, Availability Product for Purchase Decision in E-Commerce in Jakarta - Dian Meliantari; Achmad Tarmizi (CV. Rayyan Dwi Bharata, 2026)
Studies examining product availability have remained limited, despite the fact that product availability has played an important role in influencing purchasing decisions, particularly in e-commerce platforms. Many consumers have experienced disappointment after deciding to purchase a product only to discover that the desired item was unavailable. In some cases, sellers replaced the unavailable product with alternative options, such as different colors, sizes, or models that were still in stock. Under such circumstances, consumers generally faced two possible choices. First, they proceeded with the purchase by selecting an alternative color, size, or model. Second, they canceled the purchase and searched for the desired product at another store. Purchase cancellations could negatively affect sellers because potential customers might switch to competing stores, resulting in lost sales opportunities. Price also played a crucial role in determining whether consumers decided to purchase a product. Consumers on e-commerce platforms typically searched for products and compared prices across multiple stores before making a purchase decision. Therefore, even relatively small price differences could influence consumer preferences, as lower prices tended to attract buyers. Furthermore, only a limited number of studies had investigated whether perceived value mediated the relationship between price and product availability and purchasing decisions. This study employed a quantitative research design involving a sample of 100 respondents. Data were analyzed using the Partial Least Squares (PLS) method. The results indicated that price and product availability did not have a significant effect on perceived value. However, price, product availability, and perceived value were found to have significant effects on purchasing decisions. In addition, perceived value did not significantly mediate the relationships between price and purchasing decisions or between product availability and purchasing decisions. These findings suggested that consumers tended to consider price and product availability directly when making purchasing decisions rather than through the formation of perceived value. The expected output of this study was publication in an accredited national journal.